Effect of Manure Dosage on the Growth and Yield of Bambara Beans through a Multilocation Test - Sambodo, Reo; Setyoko, Agus; Sudrajat, Ajat (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The purpose of this study is to determine the suitability and productivity level of Bambara beans in the Special Region of Yogyakarta, especially to determine and examine the effect of the use of organic fertilizer from livestock manure on the growth and yield of Bambara beans. The implementation of the study involved a multi-location test of Bambara bean cultivation in three subdistricts, namely Tempel, Sedayu, and Cangkringan. In these three areas, manure was applied with 3 dose variations, namely 10 tons/Ha, 20 tons/ha and 30 tons/ha. The study was arranged in a Completely Randomized Design (CRD) where each treatment was carried out with 3 replication plots. The test results showed that the dose of manure was not significantly different from the production of Bambara beans. Therefore, a dose of manure of 10 tons/ha can be recommended to achieve higher economic benefits in Bambara bean cultivation. In addition, based on the evaluation of the growth phase and plant yield, the location of Bambara bean planting in Tempel gave higher yields compared to Sedayu and Cangkringan. Bambara bean cultivation in Tempel can produce 686.45 g/plot. Keywords: Bambara beans, Growth, Multilocation test, Organic fertilizer, Yield.